2003
DOI: 10.1074/jbc.m209235200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change in Aspartate Aminotransferase on Substrate Binding Induces Strain in the Catalytic Group and Enhances Catalysis

Abstract: Aspartate aminotransferase has been known to undergo a significant conformational change, in which the small domain approaches the large domain, and the residues at the entrance of the active site pack together, on binding of substrates. Accompanying this conformational change is a two-unit increase in the pK a of the pyridoxal 5-phosphate-Lys 258 aldimine, which has been proposed to enhance catalysis. To elucidate how the conformational change is coupled to the shift in the aldimine pK a and how these changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Extensive investigations on the biochemical properties of transaminases have provided detailed understanding of the reaction mechanism, especially with aspartate aminotransferase (AspAT) and aromatic amino acid aminotransferase (AroAT) (Hayashi et al 2003;Kagamiyama and Hayashi 2001;Hirotsu et al 2005;Kawaguchi et al 1997;Islam et al 2000;Malashkevich et al 1995;Okamoto et al 1999). 5-TA catalyzes transfer of an amino group from a primary amine to a carbonyl compound mediated by PLP (Shin and Kim 2002).…”
Section: Reaction Chemistrymentioning
confidence: 99%
“…Extensive investigations on the biochemical properties of transaminases have provided detailed understanding of the reaction mechanism, especially with aspartate aminotransferase (AspAT) and aromatic amino acid aminotransferase (AroAT) (Hayashi et al 2003;Kagamiyama and Hayashi 2001;Hirotsu et al 2005;Kawaguchi et al 1997;Islam et al 2000;Malashkevich et al 1995;Okamoto et al 1999). 5-TA catalyzes transfer of an amino group from a primary amine to a carbonyl compound mediated by PLP (Shin and Kim 2002).…”
Section: Reaction Chemistrymentioning
confidence: 99%
“…It was shown that strain in the internal aldimine, caused by the torsion between the PLP pyridine ring and the imine C4′=Nζ bond (Figure 2), plays a considerable role in the transaldimination reaction catalyzed by aspartate aminotransferase. 2,3 Similar strain in the internal aldimine was also found in a number of structures of other PLPdependent enzymes. 2 Moreover, it was demonstrated that exposure to relatively high doses of X-ray radiation relieves the strain in the internal aldimine and even induces breakage of the C4′=Nζ bond in phosphoserine aminotransferase.…”
Section: Introductionmentioning
confidence: 80%
“…Due to structure determination of the aspartate aminotransferase, the reaction mech anism of transaminases is well understood and examined in detail [10,11,[18][19][20]. The transfer of the amino group is supported by the external cofactor PLP forming a Schiff base with the ε-amino group of the lysine on the active side of the enzyme (Lys-E), called internal aldimine.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…More precisely, the internal aldimine undergoes transamination with the amino group of the substrate to create the external aldimine. But it is important that either the internal aldimine is protonated and the amino group is not or the internal aldimine is deprotonated and the amino group is protonated for the extra proton that can be transferred between the amino group of the substrate and the imine nitrogen of the aldimine [19]. The Michaelis-Menten complex formed possesses the proton on the imine nitrogen and the free amino group of the substrate.…”
Section: Reaction Mechanismmentioning
confidence: 99%